Interplay of magnetism and superconductivity in thulium and lutetium nickel-borocarbides - Blundell, S; Brown, SR; Chow, K; Cooke, D; Cox, S; Cottrell, S; Godart, C; Gupta, L; Hossain, Z; Lichti, R; MorrobelSosa, A; Mazumdar, C; et al. (1996)
Implanted muon spectroscopy shows that magnetic order coexists with superconductivity in TmNi2B2C. The muon response indicates that large amplitude fluctuations of the internal field are superimposed on a relatively small static component. The static field exhibits an unusual temperature dependence which shows no interruption at the superconducting transition and may represent evolution of a staggered or spiral arrangement of Tm moments. The dynamic component changes its spectral density at the superconducting transition and the question arises as to whether this is associated with Ni moment formation and fluctuation. In LuNi2B2C, where the rare earth ion is nonmagnetic, no signature of static order is seen. An intriguing change in the muon response does occur below about 4 K in this material; this seems suggestive of Ni moment fluctuation, although the evidence is not entirely conclusive.